Pertubuhan Jamaah Islah Malaysia (JIM): an analysis on its philosophy of education (1990-2000) - Malik, Maszlee; Abdul Rahmaan, Ahmad Fuad; Mat, Hamidah (Jabatan Sejarah dan Tamadun Islam, Universiti Malaya, 2016)
Pertubuhan Jamaah Islah Malaysia, also known as JIM was established on July 20, 1990 with the aim to bring reform to Malaysian society. With the motto Â“(Together) With Islam (We) Build the SocietyÂ”, JIM aims in reforming the society to embrace the ideal of Syumuliyyah or understanding Islam as a complete way of life, and its implementation on the life of the society. It based its ideals mainly on the al-Ikhwan al-Muslimun (Muslim Brotherhood)’s manhaj taghyir (means of reform), which starts with the building of individuals, then the families and ultimately the society. This paper will descriptively explain the philosophy of education adopted by Pertubuhan Jamaah Islah Malaysia (JIM) inspired by two major principles, Islah (reform) and Tarbiyyah (holistic education) through an inductive reading of literatures, modules and statements made by JIM from the year 1990 to 2000. This paper will also analytically investigate on the adherence of JIM to the principles and their articulation by looking into JIM’s theoretical discourse and activities since its establishment until the year 2000.